LEGAL PROTECTION IN PARTNERSHIP AGREEMENTS FOR THE PROCUREMENT OF GOODS AND CONSTRUCTION SERVICES BY MICRO, SMALL AND MEDIUM ENTERPRISES - Simbolon, David Julianto; Panjaitan, Hulman; Saragi, Paltiada (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
In conclusion, the procurement of goods and services by the government plays a critical role in driving Indonesia's development. As we have seen, this process not only contributes to economic growth through essential infrastructure projects but also fulfills the government's obligation to meet the needs of its citizens. Collaborations between the government and Micro, Small, and Medium Enterprises (MSMEs) are vital in ensuring that these efforts are effective and mutually beneficial. By fostering partnerships based on trust and shared goals, both the government and MSMEs can strengthen their capabilities to support national progress. Ultimately, a strategic approach to procurement will pave the way for sustainable development, benefiting all layers of society while enhancing the overall resilience of Indonesia's economy.This research is a normative juridical research with a statutory approach. The author uses secondary data using primary, secondary, and tertiary legal materials. The method of analysis used is qualitative method. The author concludes that the form of MSME Partnership cooperation is regulated in Law No. 11 of 2020 concerning Job Creation, including partnership patterns such as Inti-plasma, subcontracting, franchising, and others, which are also explained in Government Regulation No. 7 of 2021. Legal protection for MSMEs is regulated in several laws, and partnership cooperation provides good protection through coaching and development that includes financing, infrastructure, training, and market access. If there are any disputes related to the partnership, the responsibilities and problem solving are clearly stipulated in the agreement.